2021
DOI: 10.3390/biomedicines9121926
|View full text |Cite
|
Sign up to set email alerts
|

miR-6315 Attenuates Methotrexate Treatment-Induced Decreased Osteogenesis and Increased Adipogenesis Potentially through Modulating TGF-β/Smad2 Signalling

Abstract: Methotrexate (MTX) treatment for childhood malignancies has shown decreased osteogenesis and increased adipogenesis in bone marrow stromal cells (BMSCs), leading to bone loss and bone marrow adiposity, for which the molecular mechanisms are not fully understood. Currently, microRNAs (miRNAs) are emerging as vital mediators involved in bone/bone marrow fat homeostasis and our previous studies have demonstrated that miR-6315 was upregulated in bones of MTX-treated rats, which might be associated with bone/fat im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…A study analyzed miRNAs for elucidating changes in mTOR pathway activation following T10 SCT [ 38 ]. Another study indicated that miR-6315 may participate in osteogenesis/adipogenesis by regulating the TGF-β/Smad2 signaling pathway [ 39 ]; however, no study has focused on miR-6315 in SCI. The in vivo and in vitro experiments revealed that the expression of miR-6315 was significantly up-regulated after SCI or Glu treatment, and the results were consistent with sequencing results.…”
Section: Discussionmentioning
confidence: 99%
“…A study analyzed miRNAs for elucidating changes in mTOR pathway activation following T10 SCT [ 38 ]. Another study indicated that miR-6315 may participate in osteogenesis/adipogenesis by regulating the TGF-β/Smad2 signaling pathway [ 39 ]; however, no study has focused on miR-6315 in SCI. The in vivo and in vitro experiments revealed that the expression of miR-6315 was significantly up-regulated after SCI or Glu treatment, and the results were consistent with sequencing results.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of miR-214-5p also decreased TGF-β, p-Smad2, and collagen type IV α1 chain (COL4A1) protein expression in human BMSCs [ 216 ]. Another miRNA miR-6315, was found to promote osteogenic differentiation and to alleviate methotrexate (MTX)-induced increased adipogenesis [ 217 ]. MTX is an antimetabolite-based cancer chemotherapeutic agent proven to induce bone loss and bone marrow adiposity [ 218 ] It was also shown that the effects of miR-6315 involvement in osteogenesis/adipogenesis regulation is potentially via inhibition of TGF-β/Smad2 signalling.…”
Section: Microrna Regulation Of the Smad Cascadesmentioning
confidence: 99%
“…MTX is an antimetabolite-based cancer chemotherapeutic agent proven to induce bone loss and bone marrow adiposity [ 218 ] It was also shown that the effects of miR-6315 involvement in osteogenesis/adipogenesis regulation is potentially via inhibition of TGF-β/Smad2 signalling. MiR-6315 might be applied as a potential therapeutic target in treatment of long-term skeletal side effects from intensive chemotherapy [ 217 , 218 ].…”
Section: Microrna Regulation Of the Smad Cascadesmentioning
confidence: 99%